The Comparative Law Perspective Of Surrogation: Indonesia And Several Countries That Legalized Surrogation - Ni Nyoman Putri Purnama Santhi (Kertha Patrika, 2019)
In Vitro Fertilization (IVF) program is generally used by married couples who find difficult to have progeny that the wife has difficulty getting pregnancy so she cannot raise her fetus in her own womb. The IVF is a method of assisted reproduction in which male sperm and female egg cells are combined in a cup laboratory where fertilization occurs. One of the specific reasons for the IVF program is because a pregnancy cannot be medically possible because of the risk of danger so that it is not acceptable for the wife's health. This causes urgency to need another woman's womb in raising a fetus by providing a number of material rewards or compensation based on an agreement agreed between the intended parent and other women. After giving birth, then the child should be returned to the intended parent but not to the woman who lent her womb. This is referred to as a surrogate mother. This article is a normative legal research examines and analyses legal sources. It aims to identify legal aspects of surrogate mother not only law in Indonesia but also the law of other countries. This research indicates that regulation of surrogate mother specifically has not been regulated in Indonesian positive law. From a comparative legal perspective, it also discovers that some countries that legalize surrogation basically based on civil rights.